A tensão entre conservação e mudança no gênero nota de repúdio - Sousa, Hugo Henrique Trajano de (2024)
This investigation aims to analyze traces of permanence and change under a historical-diachronic perspective in notes of repudiation published in print newspapers and social media from Ceará (state from Brazil) institutions between the 20th and 21st centuries. For this purpose, we traced specific objectives: i) describe the socialhistorical and political environment that engenders the corpus repudiation notes; ii) recognize how gender support and media can contribute the gender verbal and nonverbal permanence and changes; iii) identify typical repudiation notes linguisticdiscursive elements which characterize discourse traditions. Our theoretical basis is grounded in the Bakhtin Circle sociocultural perspective, Rhetorical Genre Studies, English for Specific Purposes, and the paradigm of Discourse Traditions. Regarding methodology, we employ the inductive approach, the historical- comparative procedure, and documentary and bibliographic research methods. In order to recognize the repudiation note historical trajectory, we compiled a corpus of 68 gender samples published from 1964 to 2022 in the print versions of the newspapers: O Povo, O Estado, Tribuna do Ceará and Diário do Nordeste and on the social media from Ceará's institutions. Our research covers a period of 59 years, divided into six distinct phases: a) 19641973; b) 19741983; c) 19841993; d) 19942003; e) 20042013; f) 20142022. For corpus analysis, we draw on the theoreticalmethodological approach of Zavam (2017), which proposes six co(n)textual categories for a diachronic study of genres. Among the research findings, regarding the category "ambiance," we found that sociohistorical, political, and technological configurations contributed to the greater or lesser frequency of publication of repudiation notes during the analyzed period. For the "interlocutors," we observed that the genre typically expresses the opinion of institutions and maintains a regular social audience, composed, for example, of the author's socioprofessional class, the victim, and the repudiated actions accused. Concerning the "purpose," we identified eight communicative purposes in our corpus, which can be interpreted as face attack and/or saving strategies. Considering the "content," we found that since the 1980s, repudiation notes frequently discuss topics previously prohibited by the Brazilian military regime, such as aggressions committed against press professionals and attacks on freedom of expression. For the "norm," the data showed that the genre emerges in most cases from representative class institutions and has a relatively stable rhetorical organization, with units and subunits of information varying across each generational phase. Finally, in the analysis of the "form" category, we found that our object of study did not have a specific place on the pages of print newspapers and that the possibilities of social media, in the online context, provided the authors with new ways to materialize and interact through this discourse tradition. Based on our global results, we conclude that the repudiation note is a traditional cultural communication artifact in our society. The genre brings in its constitution typical and recurrent traits, which are variable at the same time, and that part of them have undergone some reworking over time.